Genebank standards - Food and Agriculture Organization of the United Nations; International Plant Genetic Resources Institute (1994)
FAO and IBPGR have been cooperating since the early 1970s to strengthen national capabilities in ex situ conservation of plant genetic resources. In 1991, the Commission on Plant Genetic Resources considered it ”essential that appropriate standards be developed for genebanks operating within the international Network”. The Commission requested the assessment and, if necessary, redefinition of genebank standards. Subsequently, an FAO/IBPGR Expert Consultation was convened in 1992 to discuss and update the Genebank Standards that IBPGR published in 1985. The Genebank Standards recommended by the Expert Consultation were then endorsed by the 5th Session of the Commission on Plant Genetic Resources to be widely utilized as the international reference in national, regional and international genebanks. The Genebank Standards are concerned solely with the storage of seed of orthodox species. (Arabic, Chinese, French and Spanish versions available)